2015
DOI: 10.1007/s10071-015-0878-9
|View full text |Cite
|
Sign up to set email alerts
|

Waiting for what comes later: capuchin monkeys show self-control even for nonvisible delayed rewards

Abstract: Self-control tasks used with nonhuman animals typically involve the choice between an immediate option and a delayed, but more preferred option. However, in many self-control scenarios, not only does the more impulsive option come sooner in time, it is often more concrete than the delayed option. For example, studies have presented children with the option of eating a visible marshmallow immediately, or foregoing it for a better reward that can only be seen later. Thus, the immediately available option is visi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 23 publications
6
19
0
Order By: Relevance
“…These findings were consistent across various short delay lengths and reward magnitudes (Bramlett et al 2012). When reward visibility (though not reward type) was manipulated in a further study, capuchins still performed well, even when only the immediate, less preferred option was visible and the delayed option was hidden, or the baiting process took place out of sight of subjects (Perdue et al 2015). The authors highlight that temporal delays are intuitive in this design as the subjects can directly observe the rewards moving closer to them (Perdue et al 2015).…”
Section: Introductionsupporting
confidence: 66%
See 2 more Smart Citations
“…These findings were consistent across various short delay lengths and reward magnitudes (Bramlett et al 2012). When reward visibility (though not reward type) was manipulated in a further study, capuchins still performed well, even when only the immediate, less preferred option was visible and the delayed option was hidden, or the baiting process took place out of sight of subjects (Perdue et al 2015). The authors highlight that temporal delays are intuitive in this design as the subjects can directly observe the rewards moving closer to them (Perdue et al 2015).…”
Section: Introductionsupporting
confidence: 66%
“…In children, when the immediate reward is visible (and delayed reward not visible), performance typically suffers, whereas when the delayed reward is visible (and immediate reward is not), this sometimes improves self-control (Mischel et al 1972). However, in capuchin monkeys, subjects continued to perform well even when the delayed option was not visible (Perdue et al 2015).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…One monkey, Nkima, had no previous experience in self-control tasks such as those used in the present study. All remaining monkeys had experience in computerized self-control tasks (Evans and Beran, 2014; Evans, Perdue, Parrish, and Beran, 2014), as well as with the accumulation task (Addessi et al, 2013) and the rotating tray task (Bramlett et al, 2012; Perdue et al, 2015). …”
Section: 1 Experimentsmentioning
confidence: 99%
“…Some researchers have argued that quantitative reward differences are less likely to promote or sustain delay of gratification than qualitative differences (e.g., Hillemann, Bugnyar, Kotrschal, and Wascher, 2014), but in this case, many of the monkeys we tested also proved successful in waiting for the larger piece of food. In a follow-up study, we presented new conditions in which the food items were first shown to the monkeys and then placed into opaque containers rather than being visible throughout the trial (Perdue, Bramlett, Evans, and Beran, 2015). …”
Section: 1 Introductionmentioning
confidence: 99%